Understanding Investment Decisions Behavior: The Effects of Age-Based Investment Behavior, Risk Tolerance, and Financial Literacy Mediated by Investment Self-Efficacy - Badriatin, Tine; Suryanugraha, Dim Zarita; Hilman, Nadia Ulfa Agustin; Lestari, Nadya Ayu (Almana : Jurnal Manajemen dan Bisnis, 2025)
The Indonesian capital market has seen significant growth, with a notable increase in investors, especially post-COVID-19 due to rising interest in digital investment tools. However, this growth doesn't always correlate with optimal investment decision-making quality. In Indonesia's complex stock market, investor behavior is a critical research area. Variables like age-based investment behavior, risk tolerance, and financial literacy significantly influence investment decisions. This influence, however, is not always direct, as investment self-efficacy can act as a crucial psychological mediator. Understanding these interrelationships is vital for both academic insights and developing effective financial education and investor protection policies in Indonesia. This quantitative survey study aims to comprehensively identify, analyze, and test the relationships between these variables using Structural Equation Modeling (SEM). Parameter estimation results indicate that X2 and x3 positively and significantly influence Y, while X1 does not show a significant effect on Y. Furthermore, Y has a highly significant positive impact on Z. Overall, these findings largely support the hypotheses, reinforcing the roles of financial literacy and X2 as significant determinants of Y, and Y's mediating role on Z.